2020
DOI: 10.3390/jcm9093016
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Blood-Based Diagnostic Biosignatures for Alzheimer’s Disease via Automated Machine Learning

Abstract: Alzheimer’s disease (AD) is the most common form of neurodegenerative dementia and its timely diagnosis remains a major challenge in biomarker discovery. In the present study, we analyzed publicly available high-throughput low-sample -omics datasets from studies in AD blood, by the AutoML technology Just Add Data Bio (JADBIO), to construct accurate predictive models for use as diagnostic biosignatures. Considering data from AD patients and age–sex matched cognitively healthy individuals, we produced three best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 35 publications
0
29
0
1
Order By: Relevance
“…Revisiting a given experimental observation is scientifically essential for maximum conclusion extraction as new and powerful statistical and computational methods are introduced. Numerous bioinformatic studies analyzing high-dimensional datasets of various modalities [ 25 , 26 , 27 ] have produced significant knowledge for BrCa biology, whereas applications of ML approaches have recently become spearheads for building powerful classifiers with major advantages towards diagnostic clinical applications [ 9 , 28 , 29 ]. Here, our ambition has been to exploit genome-wide BrCa methylation datasets through bioinformatic analysis using readily available tools in order to identify DMGs, to reveal pathophysiological implications by functional analysis and most importantly to build accurate and simple predictive signatures by means of feature selection, to be exploited in personalized BrCa management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Revisiting a given experimental observation is scientifically essential for maximum conclusion extraction as new and powerful statistical and computational methods are introduced. Numerous bioinformatic studies analyzing high-dimensional datasets of various modalities [ 25 , 26 , 27 ] have produced significant knowledge for BrCa biology, whereas applications of ML approaches have recently become spearheads for building powerful classifiers with major advantages towards diagnostic clinical applications [ 9 , 28 , 29 ]. Here, our ambition has been to exploit genome-wide BrCa methylation datasets through bioinformatic analysis using readily available tools in order to identify DMGs, to reveal pathophysiological implications by functional analysis and most importantly to build accurate and simple predictive signatures by means of feature selection, to be exploited in personalized BrCa management.…”
Section: Discussionmentioning
confidence: 99%
“…JADBio has previously been successfully used to produce signatures for clinical applications such as the development of lung cancer between smokers [ 29 ] or suicide amongst depressive patients [ 30 ]. Only recently, by revisiting publicly available -omics datasets via JADBio, we were able to deliver accurate highly-performing blood-based predictive biosignatures in Alzheimer’s disease [ 28 ] and classifiers for metastatic BrCa based on novel circulating cell free DNA methylation patterns [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…JADBio has previously been successfully used to produce signatures for clinical applications such as development of classifiers for metastatic BrCa based on novel ccfDNA methylation patterns [ 16 ], identification of risk of lung cancer in smokers [ 72 ] or suicide prediction among depressive patients [ 73 ]. Recently, by revisiting publicly available omics datasets via JADBio, we were able to deliver accurate highly-performing blood-based predictive biosignatures in Alzheimer’s disease [ 74 ] and in breast cancer [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was identified that RF classifier predicts AD with more effectively. To identify the presence of AD, three different diagnostic biosignatures were produced in [64] and the performance metrics were validated through AutoML tool JADBIO. The produced biosignatures were based on blood miRNA, mRNA, and protein, respectively.…”
Section: ) Ml-based Approaches In Ad Diagnosismentioning
confidence: 99%